Confucius and the Division of China - (:unkn) unknown (My University, 2015)
The religion known as Confucianism has been a prevalent part of Chinese society since before the time of the first Chinese Emperor of the Qin Dynasty. Confucianism has affected the identity of the Chinese people in their views of morality, family, governing, foreign affairs, and other religions like Daoism, Buddhism, Christianity, and Islam. Confucianism has been synonymous with Chinese religion and philosophy to the point that it has brought about many political reforms, revolts, and wars. Confucianism would also bring about the division of Chinese society. In my research paper, I will go through detailing how Confucianism as a religious practice and a large piece of a cultural identity became a dividing matter between two influential leaders and would divide the nation in two. Mao Zedong and the supporters of the May Fourth Movement that publicly criticized Confucianism and would go on to create the People's Republic of China on one side. On the other stands Chiang Kai-shek and the supporters of the New Life Movement, that hoped to better the nation through a frenewed focus on Confucian ideals mixed with Christianity, who would go on to create The Republic of China in Taiwan. Chiang Kai-shek with his Nationalist government style against Mao Zedong's Communist government style in the Chinese Civil War was brought on by the continued debate and conflict of ideas over whether to maintain Confucianism as a major portion of Chinese Society. This conflict still remains today after both of these leaders have reached the end of their lives. It is my hopes that through my research I will be able to state the truth behind how a philospher from before the Common Era was capable of bringing about a civil war through his words and the words of his followers.